Peutz-Jeghers syndrome in pediatric patients: experience in a tertiary care institution in Mexico - Rodrigo Ortegón-Gallareta; Rodrigo Vázquez-Frías; Gerardo Blanco-Rodriguez; Alejandra Consuelo-Sánchez; Claudia Jimena Ortiz-Rivera; Juan Rafael Murillo-Eliosa; Alan I. Vicenteño-León; Pedro Valencia-Mayoral (Permanyer, 2022)
Background: Peutz-Jeghers syndrome (PJS) is a rare autosomal dominant inherited disease characterized by the development of polyps in the gastrointestinal tract, mucocutaneous pigmentation, and the risk of developing malignant neoplasms. This study aimed to analyze the epidemiological, clinical, and histopathological data of patients with PJS treated in a tertiary pediatric hospital. Methods: We conducted a retrospective observational study to describe the epidemiological, clinical, endoscopic, and histological characterization of patients with PJS treated in a tertiary pediatric hospital in Mexico. Results: We included 13 cases with a male-female ratio of 1.16:1. Abdominal pain was the main reason for consultation, followed by rectorrhagia. Patients showed mucocutaneous pigmentation and polyps in the gastrointestinal tract, frequently of the hamartomatous type, although inflammatory polyps, follicular hyperplasia, and adenomatous polyps were also found. Among the complications, there was a high prevalence of emergency surgery secondary to abdominal obstructive processes, the main reason for first-time consultation in these patients. Conclusions: The main clinical manifestations were mucocutaneous pigmentation, abdominal pain, and rectorrhagia. PJS should be included in the differential diagnosis in the presence of intestinal obstruction. The diagnosis of PJS should not be excluded if hamartomatous polyps are not evident on the first endoscopy. Nutritional assessment should be included due to the risk of presenting some degree of malnutrition.